Internalisasi Nilai Toleransi melalui Pendidikan Agama Islam: Studi Kasus Pencegahan Intoleransi di SMA Negeri 1 Kilo Kabupaten Dompu - Arif Rahman (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
Education is fundamentally a strategic process for shaping the quality of human resources, not only in terms of intellectual competence, but also emotional maturity, social sensitivity, and spiritual awareness. In a plural school environment, education also has an important function in building attitudes of respect, openness, and peaceful coexistence among students. This study aims to analyze the role of Islamic Religious Education (PAI) in preventing intolerance at SMA Negeri 1 Kilo in Dompu Regency. The study used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, and school stakeholders. The findings show that PAI plays a significant role in preventing intolerance through the structured and contextual internalization of tolerance values. This role is realized through the integration of tolerance values into learning materials, the use of dialogue-based and inclusive teaching methods, and the reinforcement of a moderate religious culture in the school environment. PAI learning also encourages students to understand religious teachings as a source of ethics, compassion, and social responsibility. Therefore, PAI can function as a preventive educational instrument that strengthens religious moderation and supports the creation of a harmonious, inclusive, and tolerant school climate.